Edaravone ameliorates the adverse effects of valproic acid toxicity in small intestine - YARAT, AYŞEN; ALTURFAN, EBRU IŞIK; OKTAY, NİHAL ŞEHKAR; AKBAY, TUĞBA (SAGE PUBLICATIONS LTD, 2015)
Valproic acid (VPA) is a drug used for the treatment of epilepsy, bipolar psychiatric disorders, and migraine. Previous studies have reported an increased generation of reactive oxygen species and oxidative stress in the toxic mechanism of VPA. Edaravone, a free radical scavenger for clinical use, can quench free radical reaction by trapping a variety of free radical species. In this study, effect of edaravone on some small intestine biochemical parameters in VPA-induced toxicity was investigated. Thirty seven Sprague Dawley female rats were randomly divided into four groups. The groups include control group, edaravone (30 mg(-1) kg(-1) day(-1)) given group, VPA (0.5 g(-1) kg(-1) day(-1)) given group, VPA + edaravone (in same dose) given group. Edaravone and VPA were given intraperitoneally for 7 days. Biochemical parameters such as malondialdehyde, as an index of lipid peroxidation(LPO), sialic acid (SA), glutathione levels and glutathione peroxidase, glutathione-S-transferase, superoxide dismutase, catalase, myeloperoxidase, alkaline phosphatase (ALP), and tissue factor (TF) activities were determined in small intestine samples by colorimetric methods. Decreased small intestine antioxidant enzyme activities, increased LPO and SA levels, and increased activities of ALP and TF were detected in the VPA group. Based on our results edaravone may be suggested to reverse the oxidative stress and inflammation due to VPA-induced small intestine toxicity.
Keywords: Valproic acid; edaravone; intestine; antioxidant and oxidant parameters; tissue factor activity; sialic acid; TISSUE FACTOR ACTIVITIES; FREE-RADICAL SCAVENGER; ERYTHROCYTE GLUTATHIONE; SUPEROXIDE-DISMUTASE; ANTIEPILEPTIC DRUGS; LIPID-PEROXIDATION; CEREBRAL-ISCHEMIA; SIALIC-ACID; CHILDREN; PLASMA